RENÉ DESCARTES: TEMATIZATION OF GOD MINUS INTEREST IN GOD’S SUBJECT - Smolyaga, M. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The thematic motive of «God», and of «action on God» in René Descartes’s philosophy is considered as means of production of philosophical contents, and, at the same time, as «natural formation» of the same work as «real process» and as having «discursive» potential concerning fixation and an explication of the type and structure of philosophical undertaking, called classical European rationalism.